GRINDING BODIES. PROBLEMS. PERSPECTIVE - A. N. Krutilin; N. I. Bestuzhev; A. N. Bestuzhev; D. N. Kalenkovich (Литьë и металлургия)
The problems and perspectives of increasing of the grinding balls service life, which are widely used in coment industry, are shown.